PENGARUH PERMAINAN BERBURU HARTA KARUN TERHADAP KECERDASAN LOGIKA MATEMATIKA PADA ANAK USIA 5-6 TAHUN DI TK SHANDY PUTRA TELKOM PEKANBARU - Anna Veronika; Zulkifli Zulkifli; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the treasure hunt game on logical mathematical intelligence of children aged 5-6 years in TK Shandy Putra Telkom Pekanbaru. Research using experimental method with pretest posttest control group design. Population in this study were children aged 5-6 years, amounting to 75 children and the sample used in this study were 30 children divided into two classes, experimental class and control class. The data collection technique used is observation. Technique of data analysis using t-test by using program of SPSS 24. The research hypothesis that there is the effect of treasure hunt game on logical mathematical intelligence of children aged 5-6 years in TK Shandy Putra Telkom Pekanbaru. Based on data analysis known tcount = 46,403> t table = 2.145 with Sig. (2-tailed) = 0.000. because Sig <0,05 can be concluded that there is difference in logical mathematical intelligence before and after the use of treasure hunt game. Can be interpreted that there is effect of treasure hunt game on logical mathematical intelligence of children aged 5-6 years in TK Shandy Putra Telkom Pekanbaru which significant equal 51.33%Keywords: Logical Mathematical Intelligence, Treasure Hunt Game.